Confidently chill : an anxiety workbook for new adults - Balan, Duygu; Balan, Yener; Balan, Nadir (New York, NY : Routledge, 2025)
"Confidently Chill is a groundbreaking two-book set comprising an evidence-based medical workbook and a captivating graphic novel. Delving into anxiety's societal, familial, and individual dimensions, this unique resource offers practical strategies rooted in empirical research, clinical methodologies, and psychological theory. Seamlessly blending medical expertise with award-winning artistry, Confidently Chill promises a holistic journey towards identity formation and lasting healing amidst today's unprecedented challenges"--
"A Productivity Press book".
Keywords: Anxiety; Self-actualization (Psychology); Calmness; BUSINESS & ECONOMICS / Leadership